ANALISA KELAYAKAN RENCANA PEMBANGUNAN SARANA PENYEDIAAN AIR BAKU DEMPO TENGAH KOTA PAGARALAM - Delli Noviarti Rachman (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
The need for raw water for a variety of clean water, needs for households, public places and industries will continue to increase in line with the speed of development in various sectors and fields, as well as the ever-increasing population. On the other hand, the amount of raw water supply and infrastructure available today is still relatively limited, so it has not been able to meet all these needs, especially during the dry season. This, if left unchecked, will have a negative impact on the welfare and health of the community and its environment. Dempo sub-district is located in Pagaralam city, is a developing area that needs raw water to meet the needs in the region. Based on the above circumstances, and to meet / meet the needs of clean water Dempo Tengah city Pagaralam, the Ministry of Public Works and Public Housing plans to build a means of providing raw water Dempo Tengah city Pagaralam. But whether the development will be feasible or not, then the study of clean water needs analysis for the community in 2 districts, namely Dempo Tengah and Kota PagaralamKeywords : Feasibility, raw water, development